26 After six-weeks of intensive ballet rehearsals changes in the achilles tendons structure appear whereas self-reported severity scores remain the same. (April 2019) - Anker-petersen, Charlotte; Thorborg, Kristian; Antflick, Jarrod; Aagaard, Henrik; Myers, Chris; Boesen, Anders Ploug; Hølmich, Per; Juul-Kristensen, Birgit
Abstract : Introduction: The aim was to study whether six weeks of intensive dance exposure (Swan Lake rehearsals) is a significant contributor to structural changes, symptoms, clinical signs and pain in the Achilles tendon (AT). Materials and methods: Ballet dancers from The Royal Danish Ballet Company (aged 18–41) were invited (n=79) of which sixty-three (80%) dancers participated. Baseline scans were collected with follow-up scans at six weeks. The primary outcome was quantification of AT structure with Ultrasound Tissue Characteristics (UTC) (echo-type I–IV). Secondary outcomes of interest were clinical signs and symptoms gathered from a clinical examination, self-reported symptoms, VISA-A questionnaire and pain during single-legged heel raise. UTC has previously shown to have satisfactory reproducibility and validity. Separate multilevel linear and logistic regression models were performed including time and demographic variables as covariates. Result: From baseline to follow-up there was significant decrease in distribution of UTC echo-type I (β=−3.6, p=0.001;95% CI:−5.8;−1.5) with significant increase in echo-type II (β=3.2, p<0.0001;95% CI:1.6;4.8). Significant effects were also seen, of limb (type I+III) and gender (type I+II). No significant changes were found in clinical outcomes/clinical signs and symptoms. Conclusion: The cohort of ballet dancers showed significant UTC changes, mainly a reduction of echo-type I distribution after six-weeks pre-season period rehearsing Swan Lake ballet. No changes were found in clinical outcomes/clinical signs and symptoms. However, early structural changes seem important to follow longitudinally for potential planning of secondary prevention strategies.